Exploring Visuo-Tactile Temporal Binding Window Plasticity in Obsessive-Compulsive Disorder - Francesca Rastelli; Davide Fausto Borrelli; Francesca Ferroni; Anna Di Donna; Laura Dell’Uva; Maurizio Cavazza; Matteo Tonna; Martina Ardizzi (Biological Psychiatry Global Open Science)
Background: Multisensory integration (MSI) enables the brain to combine sensory inputs by defining spatial and temporal boundaries that determine whether stimuli originate from the same event. Among these, the temporal binding window (TBW) specifically refers to the temporal range within which stimuli are perceived as simultaneous and integrated. In adulthood, TBW can be narrowed through short-term perceptual training. Altered TBW plasticity has been linked to neuropsychiatric conditions, where atypical prior weighting distorts sensory integration. This study investigates obsessive-compulsive disorder (OCD), a condition marked by heightened uncertainty and excessive reliance on real-time sensory input, potentially leading to wider MSI temporal boundaries and greater sensitivity to contingent sensory experiences. Methods: In the current study, the TBW plasticity of 31 patients with OCD and 34 healthy control participants was studied by asking them to perform a simultaneity judgment task before and after a perceptual training session designed to narrow their TBW. Results: Results showed a larger TBW with an abnormal tactile leading dominance in patients with OCD before the training session. Furthermore, patients with OCD showed a higher training gain than control participants. Conclusions: These findings suggest altered TBW plasticity in OCD, potentially linked to difficulties in using past experiences as a stable source of information and an exaggerated reliance on real-time sensory input. Understanding these MSI alterations may offer new insights into the sensory mechanisms that underlie OCD and inform future research on sensory-based interventions.